Análisis del tratamiento legal de los delitos cibernéticos en Ecuador - Tubay Tuares, Alisson Ailyn (2025)
This thesis aims to analyze the legal treatment of cybercrimes in Ecuador, considering the growing impact of information technologies on criminal behavior. It examines the current legal framework, particularly the Organic Comprehensive Criminal Code (COIP), along with secondary legislation and international agreements signed by the country. Using a qualitative and legal-dogmatic approach, the study identifies key weaknesses in the definition, prevention, prosecution, and punishment of cybercrimes. It also evaluates the performance of key institutions, such as the Attorney General's Office and the National Police, in handling these offenses. The findings reveal legal gaps, lack of technical specialization, and limited international cooperation. The study concludes with recommendations to strengthen Ecuador’s cybercrime legislation and improve state capabilities, aiming to ensure a more effective justice system in response to digital challenges.